Florida Fresh: Blueberries - Jennifer Hillan (EDIS)
This document is FCS8677, one of a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: July 2002.